“Glicerina bruta na alimentação de vacas leiteiras” - Feijó, Larissa Cardoso (2015)
The objective was to evaluate the effects of the use of crude glycerin up to 160g / kg DM on nutritional parameters, milk yield and composition, nitrogen balance and microbial protein synthesis in lactating cows in the middle third fed silage-based diets High corn and NDF. Nine Holstein x Zebu cows were used, in the middle third of lactation, distributed in three Latin squares 3 x 3, submitted to three treatments consisted of inclusion of 0, 80 and 160 g of crude glycerin / kg DM diets. The experiment consisted of three periods of 20 days each, with eleven early days for adaptation to treatment and the rest, for the data collection. The inclusion of glycerin in diets did not affect (P> 0.05) intakes organic matter (OM), crude protein (CP), neutral detergent fiber (NDF) and neutral detergent fiber corrected for ash and protein (NDFcp). For the dry matter intake (MS), the trend was quadratic (P <0.087), while for (EE) and non-fiber carbohydrate (NFC) a linear model (p <0.001). There was no effect (P> 0.05) the inclusion of on milk production and milk production corrected for 3.5% fat, either for fat percentages, total solids, nonfat dry extract, somatic cell count and urea nitrogen milk. There was a quadratic effect (P = 0.017) for the milk lactose content with the highest value of 4.29%, observed when adding 80 g glycerin / kg DM. There was a linear effect (P = 0.007) in milk protein content observed with values between 3.42 and 3.52% for the diets containing 0 and 160g / kg DM glycerin, respectively. The digestibility coefficients of DM, OM, CP, NDF and NDFcp increased (P <0.05) with the crescent inclusion of glycerin, while for NFC no effect (P> 0.05) to yield an average value of 79.54%. The urine volume decreased (P <0.05) with the inclusion of crude glycerin. There was no difference (P> 0.05) for the urinary excretion of allantoin, uric acid, total purine, allantoin ratio / total purine, absorbed purines, synthesis of microbial nitrogen compounds (Nmic) and microbial protein synthesis (PMIC). The total absorbed microbial purines and purine were not affected (P> 0.05) by the inclusion of glycerin in the diet, with averages of 132.29 and 107.39 mmol / day, respectively. There was no effect (P> 0.05) the inclusion of glycerin on nitrogen intake, nitrogen balance and ratio of retained / absorbed, with average values of 0.43 kg; 0.27 kg, and 77.41%, respectively. The amount of N absorbed (kg) and the percentage of N absorbed increased linearly (P <0.05) with the inclusion of crude glycerin, with values ranging 340-370 g / day, and the percentage of 79.19 84.96% to diets with 0 160 g / kg of crude glycerin in the diet. It was concluded that the inclusion of crude glycerin up to 160 g / kg DM in the diet of dairy cows in mid lactation third promoted different effects on the nutritional parameters, nitrogen balance and microbial synthesis, without however adversely affect production and composition of milk of cows of this category of animal and may be recommended its use to the evaluated amount and diets based on the use of corn silage and high participation of NDF.